Contribuição para o estudo da degradação da qualidade do ar na cidade do Porto - Monteiro, Ana (1989)
The main objective of this paper is to understand the qualitative and quantitative impact of Oporto's urbanization on the chemistry of the local atmosphere. As we know the high concentrations of sulphur dioxide and black smokes in the atmosphere have a tight relationship with the industrial emission sources (quantity and location), but also with the atmospheric dispersion conditions. So we tried to find the main causes, from a climatological point of view, involved in the occurrence of peaks of pollution registered at Oporto air monitoring network, from 1 April 1987 to 31 March 1989.